Efficient preparation process of artemisia health bimetallic plate

CN122771731APending Publication Date: 2026-09-18DONGTAI SHENGGANG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610810048.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-05
Publication Date
2026-09-18

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种艾草健康玻镁板高效制备工艺,解决了现有玻镁板在负载艾草活性成分时难以同时保持原有防火、力学及耐水性能,且艾草活性易丧失、生产周期长、无法实现工业化高效生产的问题

Benefits of technology

[0016]This invention discloses a highly efficient preparation process for a mugwort-based health magnesium oxide board. First, mugwort ultrafine powder and mugwort volatile oil are mixed as the core material, and a composite system of carboxymethyl chitosan and silica sol is used as the wall material. Mugwort functional microcapsules are prepared by spray drying or interfacial polymerization. Then, lightly calcined magnesium oxide, magnesium sulfate heptahydrate, water, citric acid, dihydrogen phosphate, fly ash, and wood fiber are mixed and stirred evenly according to weight to obtain a magnesium sulfate-oxygenated cementitious slurry. Finally, mugwort functional microcapsules, chopped glass fibers, and expanded perlite are added to the slurry and stirred until homogeneous. The mixture is uniformly prepared; a lower layer of fiberglass mesh is laid in a mold, the mixture is poured in, leveled, and a higher layer of fiberglass mesh is laid on top. The mixture is then cold-pressed to form a blank. The blank is placed in a microwave and hot air curing device. Microwave heating raises the internal temperature of the blank to 55–65°C and maintains it for 5–10 minutes, followed by hot air drying at 50–60°C for 2–4 hours to obtain a cured board. Finally, a composite coating of Artemisia argyi extract and nano-titanium dioxide is applied to the surface of the cured board, and after drying, the finished Artemisia argyi health magnesium oxide board is obtained. This process solves the technical problems of existing magnesium oxide boards, which struggle to maintain their original fire resistance, mechanical properties, and water resistance when loaded with Artemisia argyi active ingredients, and suffer from easy loss of Artemisia argyi activity, long production cycles, and inability to achieve efficient industrial production. This process achieves efficient and stable loading of Artemisia argyi active ingredients while maintaining the board's A1-grade fire resistance, high strength, and water resistance, giving the board lasting antibacterial and air-purifying functions, while shortening the production cycle to several hours, meeting the requirements of large-scale, efficient manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122771731A_ABST
    Figure CN122771731A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of building materials, and discloses a high-efficiency preparation process of wormwood health glass-magnesium plate, which comprises the following steps: preparing wormwood superfine powder and wormwood volatile oil composite core material, and wormwood functional microcapsules of carboxymethyl chitosan-silica sol wall material; preparing magnesium sulfite gel slurry; adding microcapsules, glass fibers and perlite to obtain a mixture; paving glass fiber mesh cloth and cold pressing to form a green body; microwave heating to 55-65 DEG C, and then hot air drying and curing at 50-60 DEG C; and coating a wormwood extract and nano titanium dioxide composite coating. The present application solves the problems of existing glass-magnesium plates, such as easy loss of activity, decreased mechanical water resistance, and long production cycle, and realizes efficient loading of wormwood active ingredients while maintaining A1-grade fireproofing, high strength and water resistance, endows the plate with durable antibacterial and air purification functions, and shortens the production cycle to several hours, which is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, and in particular to a high-efficiency preparation process for Artemisia argyi health magnesium oxide board. Background Technology

[0002] Magnesium oxide (MgO) board is an inorganic fireproof board made primarily from magnesium-based cementitious materials such as magnesium oxide, magnesium chloride, or magnesium oxysulfate, reinforced with fiberglass mesh and modified with fillers, through mixing, molding, and curing. Existing MgO boards possess advantages such as A1-level fire resistance, moisture and mildew resistance, formaldehyde and asbestos-free properties, and high mechanical strength, and are widely used in fire door linings, partition ceilings, container houses, tunnel decoration, and other construction fields. To further expand its functionality, some existing technologies attempt to add plant fibers, antibacterial agents, or air-purifying materials to MgO boards, aiming to endow the boards with health benefits.

[0003] Artemisia argyi, a traditional herb, contains volatile oils containing active ingredients such as eucalyptol, camphor, and borneol, which have well-known effects such as broad-spectrum antibacterial, antiviral, insect-repellent, and air-purifying properties. However, there are several technical obstacles to directly adding artemisia argyi to magnesium oxide boards: artemisia argyi powder or fibers tend to agglomerate and disperse unevenly in inorganic cementitious slurry; the heat-sensitive active ingredients of artemisia argyi are prone to volatilization and inactivation during high-temperature curing of the boards (usually above 60°C); untreated plant components interfere with the hydration reaction of magnesium cementitious materials, leading to decreased board strength and increased water absorption; and if low-temperature natural curing is used to protect the activity of artemisia argyi, the production cycle is as long as 7 days or more, making industrial-scale, efficient production impossible.

[0004] Therefore, how to efficiently and stably load the active ingredients of Artemisia argyi onto the magnesium oxide board while maintaining its original fireproof, mechanical, and water-resistant properties, so that it can have long-lasting antibacterial and air-purifying functions, and shorten the production cycle to adapt to large-scale manufacturing, is an urgent problem to be solved in this field. Summary of the Invention

[0005] The purpose of this invention is to provide an efficient preparation process for mugwort-based health magnesium oxide boards, which solves the problems of existing magnesium oxide boards being unable to maintain their original fireproof, mechanical, and water-resistant properties when loaded with mugwort active ingredients, and the easy loss of mugwort activity, long production cycle, and inability to achieve efficient industrial production.

[0006] To achieve the above objectives, this invention provides a highly efficient preparation process for Artemisia argyi health magnesium oxide boards, comprising the following steps: Artemisia argyi ultrafine powder and Artemisia argyi volatile oil were mixed as the core material, and a composite system of carboxymethyl chitosan and silica sol was used as the wall material. Artemisia argyi functional microcapsules were prepared by spray drying or interfacial polymerization. By weight, 100 parts of lightly calcined magnesium oxide, 35-45 parts of magnesium sulfate heptahydrate, 45-55 parts of water, 0.5-1.5 parts of citric acid, 1-2 parts of dihydrogen phosphate, 10-20 parts of fly ash, and 5-10 parts of wood fiber are mixed and stirred evenly to obtain magnesium sulfate-oxygenated cementitious slurry. Add the Artemisia argyi functional microcapsules, chopped glass fibers and expanded perlite to the magnesium sulfate oxychloride gelling slurry, stir and mix evenly to obtain a mixture; The lower layer of fiberglass mesh is laid in the mold, the mixture is poured in, the upper layer of fiberglass mesh is laid after smoothing, and the blank is obtained by cold pressing. The blank is placed in a microwave and hot air curing equipment. First, microwave heating is used to raise the internal temperature of the blank to 55-65°C and maintain it for 5-10 minutes. Then, circulating hot air at 50-60°C is used to dry it for 2-4 hours to obtain a cured board. A composite coating of Artemisia argyi extract and nano-titanium dioxide is applied to the surface of the cured board, and after drying, the finished Artemisia argyi health magnesium oxide board is obtained.

[0007] The process involves using a mixture of mugwort ultrafine powder and mugwort volatile oil as the core material, and a composite system of carboxymethyl chitosan and silica sol as the wall material. The preparation of mugwort functional microcapsules via spray drying or interfacial polymerization specifically includes: The particle size D90 of the mugwort ultrafine powder is ≤10μm, the mugwort volatile oil is extracted by steam distillation, and the mass ratio of the mugwort ultrafine powder to the mugwort volatile oil is 3:1.

[0008] The process involves using a mixture of mugwort ultrafine powder and mugwort volatile oil as the core material, and a composite system of carboxymethyl chitosan and silica sol as the wall material. The preparation of mugwort functional microcapsules via spray drying or interfacial polymerization specifically includes: The average particle size of the Artemisia argyi functional microcapsules is 20-50 μm, and the mass ratio of the core material to the wall material is 3:1 to 4:1.

[0009] The mixture, by weight, comprises 100 parts of lightly calcined magnesium oxide, 35-45 parts of magnesium sulfate heptahydrate, 45-55 parts of water, 0.5-1.5 parts of citric acid, 1-2 parts of dihydrogen phosphate, 10-20 parts of fly ash, and 5-10 parts of wood fiber, which are mixed and stirred evenly to obtain the magnesium sulfate-oxygenated cementitious slurry, specifically including: The MgO content of the lightly calcined magnesium oxide is ≥80%, and the dihydrogen phosphate is potassium dihydrogen phosphate or sodium dihydrogen phosphate.

[0010] Specifically, the Artemisia argyi functional microcapsules, chopped glass fibers, and expanded perlite are added to the magnesium oxysulfate gelling slurry and mixed evenly to obtain a mixture comprising: The amount of the Artemisia argyi functional microcapsules added is 5% to 15% of the mass of the lightly calcined magnesium oxide, the length of the short-cut glass fiber is 6 to 12 mm and the amount added is 3% to 8%, and the volume filling rate of the expanded perlite is 5% to 10%.

[0011] The process involves sequentially laying a lower layer of fiberglass mesh in a mold, pouring in the mixture, smoothing it out, laying a higher layer of fiberglass mesh, and then cold-pressing it to obtain a blank. Specifically, this includes: The cold pressing pressure is 12-18 MPa, and the holding time is 2-5 minutes.

[0012] The process involves placing the preform in a microwave and hot air combined curing device, first heating it with microwaves to raise the internal temperature to 55-65°C and maintaining it for 5-10 minutes, then drying it with circulating hot air at 50-60°C for 2-4 hours to obtain a cured board, specifically including: The microwave frequency is 2450MHz, and the power density is 10-20kW / m². 3 The temperature of the billet is controlled to not exceed 65℃ by using an infrared temperature sensor.

[0013] Specifically, the process of coating the surface of the cured board with a composite coating of Artemisia argyi extract and nano-titanium dioxide, and drying it to obtain the finished Artemisia argyi health magnesium oxide board includes: The components of the Artemisia argyi extract and nano-titanium dioxide composite coating, by mass percentage, are: Artemisia argyi alcohol extract 2%, nano-anatase titanium dioxide 1%, aqueous silicone-acrylic emulsion 15%, and the balance being deionized water; the coating weight is 80–120 g / m². 2 The drying temperature is 50℃ and the drying time is 30 minutes.

[0014] The process involves using a mixture of mugwort ultrafine powder and mugwort volatile oil as the core material, and a composite system of carboxymethyl chitosan and silica sol as the wall material. The preparation of mugwort functional microcapsules via spray drying or interfacial polymerization specifically includes: The mass ratio of carboxymethyl chitosan to silica sol in the composite system of carboxymethyl chitosan and silica sol is 1:4.

[0015] The process includes, after coating the surface of the cured board with a composite coating of Artemisia argyi extract and nano-titanium dioxide, and drying it to obtain the finished Artemisia argyi health magnesium oxide board, the process further includes: The finished product of the Artemisia argyi health magnesium oxide board is cut into the required specifications, left to stand for 24 hours in an environment with room temperature and relative humidity ≤60%, and then packaged and stored.

[0016] This invention discloses a highly efficient preparation process for a mugwort-based health magnesium oxide board. First, mugwort ultrafine powder and mugwort volatile oil are mixed as the core material, and a composite system of carboxymethyl chitosan and silica sol is used as the wall material. Mugwort functional microcapsules are prepared by spray drying or interfacial polymerization. Then, lightly calcined magnesium oxide, magnesium sulfate heptahydrate, water, citric acid, dihydrogen phosphate, fly ash, and wood fiber are mixed and stirred evenly according to weight to obtain a magnesium sulfate-oxygenated cementitious slurry. Finally, mugwort functional microcapsules, chopped glass fibers, and expanded perlite are added to the slurry and stirred until homogeneous. The mixture is uniformly prepared; a lower layer of fiberglass mesh is laid in a mold, the mixture is poured in, leveled, and a higher layer of fiberglass mesh is laid on top. The mixture is then cold-pressed to form a blank. The blank is placed in a microwave and hot air curing device. Microwave heating raises the internal temperature of the blank to 55–65°C and maintains it for 5–10 minutes, followed by hot air drying at 50–60°C for 2–4 hours to obtain a cured board. Finally, a composite coating of Artemisia argyi extract and nano-titanium dioxide is applied to the surface of the cured board, and after drying, the finished Artemisia argyi health magnesium oxide board is obtained. This process solves the technical problems of existing magnesium oxide boards, which struggle to maintain their original fire resistance, mechanical properties, and water resistance when loaded with Artemisia argyi active ingredients, and suffer from easy loss of Artemisia argyi activity, long production cycles, and inability to achieve efficient industrial production. This process achieves efficient and stable loading of Artemisia argyi active ingredients while maintaining the board's A1-grade fire resistance, high strength, and water resistance, giving the board lasting antibacterial and air-purifying functions, while shortening the production cycle to several hours, meeting the requirements of large-scale, efficient manufacturing. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.

[0018] Figure 1 This is a flowchart of the efficient preparation process of the Artemisia argyi health magnesium oxide board of the present invention. Detailed Implementation

[0019] The embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, but should not be construed as limiting the present invention.

[0020] Please refer to Figure 1 This invention provides a highly efficient preparation process for Artemisia argyi health magnesium oxide board, comprising the following steps: S101: Artemisia argyi ultrafine powder and Artemisia argyi volatile oil are mixed as core material, and a composite system of carboxymethyl chitosan and silica sol is used as wall material. Artemisia argyi functional microcapsules are prepared by spray drying or interfacial polymerization. Specifically, dried Artemisia argyi whole herb is ultra-finely pulverized to a particle size D90 ≤ 10 μm to obtain Artemisia argyi ultrafine powder. Simultaneously, Artemisia argyi volatile oil is extracted using steam distillation. This volatile oil is rich in antibacterial, antiviral, and air-purifying active ingredients such as eucalyptol, camphor, and borneol. The above Artemisia argyi ultrafine powder and Artemisia argyi volatile oil are mixed at a mass ratio of 3:1 to serve as the core material for microcapsules. The wall material is a composite system of carboxymethyl chitosan and silica sol, with a mass ratio of carboxymethyl chitosan to silica sol of 1:4. Carboxymethyl chitosan has good film-forming properties and biocompatibility, while silica sol provides an inorganic framework and thermal stability. The combination of the two can both protect the core material and enhance the dispersion stability of the microcapsules in magnesium oxysulfate slurry. The core material and wall material are mixed at a mass ratio (core material: wall material) of 3:1 to 4:1, and microcapsules are prepared using spray drying or interfacial polymerization. Typical conditions for spray drying are: inlet air temperature 160–180℃, outlet air temperature 80–90℃, and atomization pressure 0.2–0.4 MPa. Interfacial polymerization can be achieved by adding a crosslinking agent to the oil-in-water emulsion. The average particle size of the prepared Artemisia argyi functional microcapsules is controlled within the range of 20–50 μm. This particle size avoids agglomeration caused by excessive fineness while preventing excessive coarseness from affecting the surface smoothness and mechanical properties of the board. Through the above microencapsulation treatment, the active ingredients of Artemisia argyi are completely encapsulated, maintaining stability during subsequent mixing with magnesium oxide slurry, cold pressing, and microwave-hot air curing. This avoids volatilization and deactivation due to direct contact with alkaline environments and high temperatures. Simultaneously, it improves the dispersion uniformity of plant components in the inorganic matrix, laying the foundation for the subsequent preparation of magnesium oxide boards with both health functions and excellent mechanical properties.

[0021] S102: By weight, 100 parts of lightly calcined magnesium oxide, 35-45 parts of magnesium sulfate heptahydrate, 45-55 parts of water, 0.5-1.5 parts of citric acid, 1-2 parts of dihydrogen phosphate, 10-20 parts of fly ash, and 5-10 parts of wood fiber are mixed and stirred evenly to obtain magnesium sulfate-oxygenated cementitious slurry. Specifically, to avoid the problems of easy efflorescence and high water absorption rate of traditional magnesium oxychloride systems, this invention selects a magnesium oxysulfate cement system. By weight, 100 parts of lightly calcined magnesium oxide (MgO content ≥80% to ensure hydration activity and gel strength), 35-45 parts of magnesium sulfate heptahydrate, and 45-55 parts of water are used. The magnesium sulfate is pre-dissolved in water to form a magnesium sulfate solution before mixing with the magnesium oxide, which controls the hydration reaction rate. To improve the workability of the magnesium oxysulfate slurry and the water resistance of the hardened body, 0.5-1.5 parts of citric acid are added as a retarder and modifier. Citric acid can delay the hydration induction period, preventing the slurry from setting too quickly and causing molding difficulties, while also helping to form a stable magnesium oxysulfate crystalline phase. 1-2 parts of dihydrogen phosphate are added; the dihydrogen phosphate is potassium dihydrogen phosphate or sodium dihydrogen phosphate, which can form an insoluble phosphate protective film with magnesium ions on the magnesium oxide surface, significantly reducing the water absorption rate of the board and improving long-term water resistance. Adding 10-20 parts of fly ash as micro-aggregate and active filler, the spherical particles of fly ash can improve the fluidity of the slurry and participate in the hydration reaction, reducing shrinkage and increasing density. Adding 5-10 parts of wood fiber, this natural fiber can enhance the initial toughness and crack resistance of the board, and at the same time form an organic-inorganic composite structure with the subsequently added Artemisia argyi functional microcapsules, which is beneficial to improving interfacial bonding. Add the above components to a forced mixer, first dry mix for 2-3 minutes to make the powder uniform, then add magnesium sulfate solution (included in the total water volume), and continue mixing for 3-5 minutes until a uniform, lump-free slurry with suitable viscosity is obtained. The magnesium sulfate oxychloride gelling slurry obtained by the above ratio has suitable fluidity and plasticity, can uniformly encapsulate the subsequently added microcapsules, glass fibers and perlite, and provide good green body density for cold pressing. The slurry system can be rapidly hydrated during the subsequent microwave-hot air combined curing process, forming a high-strength water-resistant structure with basic magnesium sulfate whiskers as the skeleton, thereby compensating for the strength loss that may be caused by the addition of plant-based components and ensuring that the mechanical properties of the final board meet the standard requirements of A1 fireproof board.

[0022] S103: Add the Artemisia argyi functional microcapsules, chopped glass fibers and expanded perlite to the magnesium oxysulfate gelling material, stir and mix evenly to obtain a mixture; Specifically, the Artemisia argyi functional microcapsules prepared in step S101 are added to the magnesium oxysulfate slurry at a concentration of 5% to 15% of the mass of lightly calcined magnesium oxide. Experiments have verified that below 5%, the health benefits (antibacterial rate, air purification rate) are not significant, while above 15% may slightly affect the mechanical strength of the board and reduce economic efficiency. Due to the composite effect of carboxymethyl chitosan and silica sol in the wall material, the Artemisia argyi functional microcapsules are uniformly dispersed in the slurry, preventing agglomeration, and slowly release the active ingredients of Artemisia argyi during subsequent curing, achieving long-term health benefits.

[0023] Simultaneously, chopped glass fibers with a length of 6–12 mm are added at a rate of 3%–8% of the mass of light-burned magnesium oxide. As an inorganic reinforcing material, the chopped glass fibers can form a three-dimensional reinforcing network in conjunction with the fiberglass mesh, effectively compensating for any potential loss in flexural strength due to the addition of plant-based components (Artemisia argyi microcapsules, wood fiber), while simultaneously improving the impact toughness and crack resistance of the board. The fiber length should be controlled between 6 and 12 mm; too short a length will result in insufficient reinforcement, while too long a length will easily entangle and clump during mixing, affecting the uniformity of dispersion.

[0024] Expanded perlite is added as a lightweight filler, with a volumetric filling rate of 5% to 10% of the total volume of the magnesium oxysulfate cementitious mortar (excluding microcapsules and fibers). Expanded perlite has a porous structure, which can reduce the density of the board, improve thermal insulation performance, and enhance processability. When the volumetric filling rate is below 5%, the lightweight effect is not significant; above 10%, it may weaken the mechanical strength and surface density of the board.

[0025] The aforementioned Artemisia argyi functional microcapsules, chopped glass fibers, and expanded perlite are added sequentially or simultaneously to the magnesium oxysulfate mortar. The mixture is stirred for 5-8 minutes using a low-speed mixer (60-80 rpm) to avoid high-speed shearing damage to the microcapsule walls and breakage of the perlite. Stirring continues until all components are evenly distributed in the mortar, with no obvious fiber agglomeration or microcapsule floating, resulting in a homogeneous and stable mixture. This mixture exhibits good workability and water retention, providing a suitable material state for subsequent paving and cold pressing. Through the synergistic addition of these functional components, the active ingredients of Artemisia argyi are ensured to be evenly distributed within the board to achieve long-lasting health benefits, while the glass fiber reinforcement and perlite lightweighting ensure the mechanical properties and user comfort of the board.

[0026] S104: Lay the lower layer of fiberglass mesh in the mold, pour in the mixture, smooth it out, lay the upper layer of fiberglass mesh, and cold press to form a blank. Specifically, after the mixture is prepared, the sheets are laid out and cold-pressed for pre-forming to obtain a dense, flat, and uniformly structured blank. First, a molding die is prepared; the inner surface of the die should be smooth and coated with a release agent to facilitate subsequent demolding. A layer of medium-alkali fiberglass mesh (120–160 g / m²) is pre-laid at the bottom of the die. 2The lower layer of fiberglass mesh (with a 5×5mm aperture) serves as the outer reinforcing layer of the board, improving its bending strength and impact resistance. Next, the mixture obtained in step S103 is evenly poured into the mold. The amount poured is calculated based on the target board thickness, typically controlled to be 8–20mm. The surface of the mixture is smoothed using a scraper or roller to ensure uniform thickness, absence of air bubbles, or localized material shortages. Then, another layer of upper fiberglass mesh of the same specifications is laid on the smoothed surface, forming a double-sided reinforcing structure. The two layers of mesh, along with the chopped glass fibers in the mixture, work together to construct a three-dimensional reinforcing network, significantly improving the overall mechanical properties of the board.

[0027] After paving is completed, cold pressing is performed immediately. A hydraulic press or oil press is used to apply pressure, with the cold pressing pressure controlled at 12–18 MPa and the holding time at 2–5 minutes. The purpose of cold pressing is twofold: firstly, to remove air bubbles and excess moisture entrained in the mixture, improving the density and dimensional stability of the green body; secondly, to ensure a tight bond between the upper and lower mesh fabrics and the slurry, preventing delamination; and thirdly, the cold pressing process does not introduce high temperatures, effectively protecting the heat-sensitive active ingredients in the Artemisia argyi functional microcapsules and preventing premature volatilization or deactivation. If the holding time is too short, the green body will lack density and be prone to internal defects; if the holding time is too long, production efficiency will decrease and equipment requirements will increase. Within the specified pressure and time range, the green body can achieve suitable wet density and molding strength, maintaining its shape stably for the next curing process. After molding, demolding yields a green body with double-layer mesh reinforcement, uniformly distributed Artemisia argyi functional microcapsules, chopped glass fiber, and expanded perlite. The preform is in a semi-finished state, with moderate moisture content and dense structure, providing an ideal precursor for subsequent microwave-hot air co-curing.

[0028] S105: The blank is placed in a microwave and hot air combined curing equipment. First, microwave heating is used to raise the internal temperature of the blank to 55-65°C and maintain it for 5-10 minutes. Then, circulating hot air at 50-60°C is used to dry it for 2-4 hours to obtain a cured board. Specifically, the preform obtained from cold pressing in step S104 is transferred to a microwave and hot air combined curing equipment for efficient curing. This equipment is equipped with both a microwave generator and a circulating hot air system, enabling the heating and drying processes to be completed sequentially or in tandem. First, the microwave heating module is activated, with a microwave frequency of 2450MHz (industrial standard frequency) and a power density controlled at 10–20kW / m². 3This process causes the polar molecules (mainly water molecules) inside the green body to oscillate at high frequency, resulting in uniform heating. Infrared temperature sensors placed on the surface of the green body monitor temperature changes in real time and provide feedback to control the microwave output power, ensuring that the internal temperature of the green body slowly rises to 55–65°C and is maintained within this temperature range for 5–10 minutes. This temperature range is significantly lower than traditional high-temperature curing (usually ≥80°C), effectively protecting the heat-sensitive active ingredients in the Artemisia argyi functional microcapsules and preventing their volatilization or decomposition. Simultaneously, the penetrating heating of the microwaves causes the internal and external parts of the green body to heat up almost simultaneously, accelerating the hydration reaction of the magnesium sulfate cementitious material and forming a stable basic magnesium sulfate crystal phase, thereby rapidly establishing early strength. Maintaining the temperature for 5–10 minutes is sufficient to activate the hydration reaction; too short a time results in insufficient hydration, while too long a time may cause rapid vaporization of moisture, leading to internal microcracks.

[0029] After microwave heating is complete, the microwave source is turned off, and the process switches to the circulating hot air drying stage. Circulating hot air at 50–60°C is introduced, with relative humidity controlled at 30%–50% and a wind speed of 1–2 m / s, for continuous drying for 2–4 hours. The purpose of this stage is to gradually remove residual free water and some bound water from the green body, reducing the moisture content of the board to an equilibrium state (usually ≤8%), while further stabilizing the later stages of the hydration reaction. Low-temperature hot air drying avoids cracking, warping, and heat loss of the active ingredients in Artemisia argyi caused by rapid high-temperature drying. The drying time of 2–4 hours can be adjusted appropriately according to the thickness of the board and the ambient humidity to ensure that the strength, dimensional stability, and durability of the finally cured board meet the design requirements. The total time of the entire combined curing process (microwave + hot air) is controlled at approximately 2–4.5 hours, significantly shorter than traditional natural curing (more than 7 days) or simple oven heating (more than 24 hours).

[0030] After curing with a combination of microwave and hot air, the resulting cured board possesses sufficient mechanical strength (flexural strength ≥18MPa) and structural stability. The Artemisia argyi functional microcapsules remain intact, and the retention rate of Artemisia argyi active ingredients can reach over 90%. This cured board can directly proceed to the surface coating process without requiring additional long-term standing or secondary curing.

[0031] S106: Coat the surface of the cured board with a composite coating of Artemisia argyi extract and nano-titanium dioxide, and after drying, obtain the finished Artemisia argyi health magnesium oxide board.

[0032] Specifically, the surface of the cured board obtained in step S105 is further coated with a functional coating to enhance the board's antibacterial and air purification properties and create a synergistic effect with the internally distributed Artemisia argyi functional microcapsules. First, a composite coating solution of Artemisia argyi extract and nano-titanium dioxide is prepared: 2% by mass of Artemisia argyi alcohol extract, which is rich in total flavonoids and other active ingredients; 1% by mass of nano-anatase titanium dioxide, with a particle size of 10-30 nm, which has photocatalytic degradation properties for formaldehyde and VOCs and antibacterial properties; 15% by mass of water-based silicone-acrylic emulsion as a film-forming agent, imparting good adhesion and scrub resistance to the coating; the remainder is deionized water as a dispersion medium. The above components are stirred and mixed evenly in a high-speed disperser to obtain a stable and dispersed composite coating liquid. The composite coating liquid is then uniformly coated onto the upper surface and surrounding area of ​​the cured board using a roller coating or spray coating process (single-sided or double-sided coating is also possible depending on the application requirements), with a coating amount controlled at 80-120 g / m². 2 If the coating amount is too low, the functional layer will be too thin and the durability insufficient; if the coating amount is too high, it will easily cause sagging, drying cracking, and increase costs. After coating, the board is placed in a 50℃ hot air circulating drying oven for 30 minutes to promote full curing and firm adhesion of the coating to the board surface. The dried coating is transparent and crack-free. The nano titanium dioxide can catalyze the degradation of harmful gases such as formaldehyde under visible light or indoor light, while the artemisia argyi extract provides immediate antibacterial and insect-repellent effects. Together with the artemisia argyi active ingredients slowly released from the microcapsules inside the board, they form a dual health protection system of "internal slow release - external immediate".

[0033] To further improve the quality of the finished product, post-processing is carried out after the coating dries: the resulting Artemisia argyi health magnesium oxide board is cut into the required specifications according to customer needs, such as 1220×2440mm or other customized sizes. Cutting is done using a water jet or diamond saw blade, ensuring smooth edges without chipping. The cut boards are then placed in an environment at room temperature (20~25℃) and relative humidity ≤60% for 24 hours to release residual internal stress, eliminate minor deformation caused by cutting, and allow the moisture content of the boards to reach equilibrium with the environment. After the settling period, after passing appearance inspection, dimensional inspection, and performance sampling, the boards are packaged in moisture-proof packaging materials and stored, resulting in the final Artemisia argyi health magnesium oxide board product ready for market.

[0034] Through the aforementioned surface coating and post-treatment, the Artemisia argyi health magnesium oxide board of the present invention not only has uniformly distributed Artemisia argyi functional microcapsules inside, which can release Artemisia argyi active ingredients over a long period of time, but also forms a composite functional layer containing Artemisia argyi extract and nano-titanium dioxide on the surface, significantly enhancing the product's initial antibacterial and air purification efficiency. The entire preparation process, from raw materials to finished product, takes no more than 24 hours, while maintaining the board's excellent properties such as A1 fire resistance, high flexural strength, and low water absorption, achieving efficient, stable, and large-scale production.

[0035] The above-disclosed embodiments are merely one or more preferred embodiments of this application and should not be construed as limiting the scope of this application. Those skilled in the art can understand that all or part of the processes for implementing the above embodiments and equivalent changes made in accordance with the claims of this application still fall within the scope of this application.

Claims

1. A highly efficient preparation process for Artemisia annua health magnesium oxide board, characterized in that, Includes the following steps: Artemisia argyi ultrafine powder and Artemisia argyi volatile oil were mixed as the core material, and a composite system of carboxymethyl chitosan and silica sol was used as the wall material. Artemisia argyi functional microcapsules were prepared by spray drying or interfacial polymerization. By weight, 100 parts of lightly calcined magnesium oxide, 35-45 parts of magnesium sulfate heptahydrate, 45-55 parts of water, 0.5-1.5 parts of citric acid, 1-2 parts of dihydrogen phosphate, 10-20 parts of fly ash, and 5-10 parts of wood fiber are mixed and stirred evenly to obtain magnesium sulfate-oxygenated cementitious slurry. Add the Artemisia argyi functional microcapsules, chopped glass fibers and expanded perlite to the magnesium sulfate oxychloride gelling slurry, stir and mix evenly to obtain a mixture; The lower layer of fiberglass mesh is laid in the mold, the mixture is poured in, the upper layer of fiberglass mesh is laid after smoothing, and the blank is obtained by cold pressing. The blank is placed in a microwave and hot air curing equipment. First, microwave heating is used to raise the internal temperature of the blank to 55-65°C and maintain it for 5-10 minutes. Then, circulating hot air at 50-60°C is used to dry it for 2-4 hours to obtain a cured board. A composite coating of Artemisia argyi extract and nano-titanium dioxide is applied to the surface of the cured board, and after drying, the finished Artemisia argyi health magnesium oxide board is obtained.

2. The efficient preparation process of Artemisia argyi health magnesium oxide board as described in claim 1, characterized in that, Artemisia argyi ultrafine powder and Artemisia argyi volatile oil are mixed as the core material, and a composite system of carboxymethyl chitosan and silica sol is used as the wall material. Artemisia argyi functional microcapsules are prepared by spray drying or interfacial polymerization. Specifically, the preparation includes: The particle size D90 of the mugwort ultrafine powder is ≤10μm, the mugwort volatile oil is extracted by steam distillation, and the mass ratio of the mugwort ultrafine powder to the mugwort volatile oil is 3:

1.

3. The efficient preparation process of Artemisia argyi health magnesium oxide board as described in claim 1, characterized in that, Artemisia argyi ultrafine powder and Artemisia argyi volatile oil are mixed as the core material, and a composite system of carboxymethyl chitosan and silica sol is used as the wall material. Artemisia argyi functional microcapsules are prepared by spray drying or interfacial polymerization. Specifically, the preparation includes: The average particle size of the Artemisia argyi functional microcapsules is 20-50 μm, and the mass ratio of the core material to the wall material is 3:1 to 4:

1.

4. The efficient preparation process of Artemisia argyi health magnesium oxide board as described in claim 1, characterized in that, By weight, 100 parts of lightly calcined magnesium oxide, 35-45 parts of magnesium sulfate heptahydrate, 45-55 parts of water, 0.5-1.5 parts of citric acid, 1-2 parts of dihydrogen phosphate, 10-20 parts of fly ash, and 5-10 parts of wood fiber are mixed and stirred evenly to obtain magnesium sulfate-oxygenated coagulant, which specifically includes: The MgO content of the lightly calcined magnesium oxide is ≥80%, and the dihydrogen phosphate is potassium dihydrogen phosphate or sodium dihydrogen phosphate.

5. The efficient preparation process of Artemisia argyi health magnesium oxide board as described in claim 1, characterized in that, The Artemisia argyi functional microcapsules, chopped glass fibers, and expanded perlite are added to the magnesium sulfate oxychloride gelling slurry and mixed evenly to obtain a mixture that specifically includes: The amount of the Artemisia argyi functional microcapsules added is 5% to 15% of the mass of the lightly calcined magnesium oxide, the length of the short-cut glass fiber is 6 to 12 mm and the amount added is 3% to 8%, and the volume filling rate of the expanded perlite is 5% to 10%.

6. The efficient preparation process of Artemisia argyi health magnesium oxide board as described in claim 1, characterized in that, In a mold, a lower layer of fiberglass mesh is laid out sequentially, the mixture is poured in, leveled, and then a higher layer of fiberglass mesh is laid out. Cold pressing is then used to form the blank, which specifically includes: The cold pressing pressure is 12-18 MPa, and the holding time is 2-5 minutes.

7. The efficient preparation process of Artemisia argyi health magnesium oxide board as described in claim 1, characterized in that, The preform is placed in a microwave and hot air curing device. First, microwave heating raises the internal temperature of the preform to 55–65°C and maintains it for 5–10 minutes. Then, it is dried with circulating hot air at 50–60°C for 2–4 hours to obtain a cured board, specifically comprising: The microwave frequency is 2450MHz, and the power density is 10-20kW / m². 3 The temperature of the billet is controlled to not exceed 65℃ by using an infrared temperature sensor.

8. The efficient preparation process of Artemisia argyi health magnesium oxide board as described in claim 1, characterized in that, The process of coating the surface of the cured board with a composite coating of Artemisia argyi extract and nano-titanium dioxide, and drying it to obtain the finished Artemisia argyi health magnesium oxide board, specifically includes: The components of the Artemisia argyi extract and nano-titanium dioxide composite coating, by mass percentage, are: Artemisia argyi alcohol extract 2%, nano-anatase titanium dioxide 1%, aqueous silicone-acrylic emulsion 15%, and the balance being deionized water; the coating weight is 80–120 g / m². 2 The drying temperature is 50℃ and the drying time is 30 minutes.

9. The efficient preparation process of Artemisia argyi health magnesium oxide board as described in claim 1, characterized in that, Artemisia argyi ultrafine powder and Artemisia argyi volatile oil are mixed as the core material, and a composite system of carboxymethyl chitosan and silica sol is used as the wall material. Artemisia argyi functional microcapsules are prepared by spray drying or interfacial polymerization. Specifically, the preparation includes: The mass ratio of carboxymethyl chitosan to silica sol in the composite system of carboxymethyl chitosan and silica sol is 1:

4.

10. The efficient preparation process of Artemisia argyi health magnesium oxide board as described in claim 1, characterized in that, After coating the surface of the cured board with a composite coating of Artemisia argyi extract and nano-titanium dioxide, and drying it to obtain the finished Artemisia argyi health magnesium oxide board, the process further includes: The finished product of the Artemisia argyi health magnesium oxide board is cut into the required specifications, left to stand for 24 hours in an environment with room temperature and relative humidity ≤60%, and then packaged and stored.